EFFECTIVENESS OF COUNSELING THERAPY ON SEXUAL DYSFUNCTION IN WOMEN WITH DIABETES MELLITUS: A SYSTEMATIC REVIEW - Nekka Juliani; Debie Dahlia; Dikha Ayu Kurnia; Riri Maria (Universitas Kadiri, 2025)
Diabetes mellitus (DM) is a serious long-term or chronic condition that occurs when there is an increase in blood glucose levels due to the body's inability to produce enough insulin or effectively use the insulin it produces. In patients with Diabetes Mellitus, sexual dysfunction is a frequently overlooked complication, despite significantly impacting quality of life. Female sexual dysfunction is defined as a persistent or recurrent decrease in sexual desire, persistent or recurrent decrease in sexual arousal, dyspareunia, and difficulty or inability to achieve orgasm. Several variables influence sexual dysfunction, including depression, anxiety, physical problems, marital issues, and medication side effects. Additionally, social and cultural norms related to diabetes and sexuality can lead to feelings of guilt, stigma, and low self-esteem. The aim of this systematic review is to analyze the effectiveness of counseling therapy on sexual dysfunction in women with diabetes mellitus. This article conducted a search of electronic database sources including Science Direct, Springer Link, Proquest, and Scopus, published from 2014 to 2024, using several keywords: (Female Sexual Dysfunction And Diabetes Mellitus And FSFI And Counseling). Results : Based on the analysis of four articles, there is a positive relationship between counseling therapy and sexual dysfunction in women with diabetes mellitus. Conclusion and Recommendations : Holistic counseling therapy that addresses various physical, psychological, cultural aspects, and individual temperament can improve sexual function, thereby enhancing patients' quality of life. Therefore, it is important for healthcare providers to consider counseling therapy as part of the care plan for women experiencing sexual dysfunction due to diabetes.